Public awareness and knowledge about colorectal cancer screening in Saudi Arabia - Alsehemi, Zeyad Omar (International Journal Of Community Medicine And Public Health, 2024)
Background: Colorectal cancer (CRC) is a significant global health concern, ranking second among women and third among men in cancer diagnoses worldwide. In Saudi Arabia, CRC has been the most prevalent cancer in men since 2002. Despite rising incidence rates, public awareness and understanding of CRC screening remain critical for early detection and effective intervention. This study assesses public awareness and knowledge regarding CRC screening in Saudi Arabia. Methods: A cross-sectional, questionnaire-based study was conducted using Google forms to gather data from Saudi Arabia's overall population from 5th December 2023 to 20th December 2023. The online questionnaire included demographic information and assessed participants' knowledge, awareness, and attitudes toward CRC screening. Data analysis was performed using SPSS version 26. Results: Of the 461 participants, 61.4% were female, 38.6% were male, and 53.1% were 50 or older. Only 13.1% of participants aged 50 and above had undergone CRC screening. A significant proportion (55.1%) in other age groups remained undecided about future screening. Lack of awareness (51.9%) was the primary reason for refusal or hesitation. Participants exhibited limited awareness of CRC's global prevalence (50.3%) and the recommended screening age (36.4%). Significant associations were found between awareness levels, gender, education, and age groups. Conclusions: The study highlights a substantial need for more awareness and knowledge about CRC screening in Saudi Arabia, particularly among specific demographic groups. Targeted awareness campaigns are crucial, focusing on increasing knowledge about risk factors, symptoms, and the importance of early screening.